Community participation in protected area management of Taman Negara National Park, Pahang, Malaysia / Mohd Salleh Daim - Daim, Mohd Salleh (Institute of Graduate Studies, UiTM, 2016)
Within the theoretical concepts community participation has been used or explored in many fields as an approach for conflict resolution. In the field of natural resource management, recognising the rights and responsibility of local community neighbouring to natural areas has become vital to complement the traditional management approach especially in protected area management. One of the prevalent issues in the field of protected area management would be the relationship between the protected area and its neighbours. This bittersweet relationship is loaded with protected area management theories and principles adopted by most management agencies mixed with the moral, values and norms of local community who often reside within or in close proximity to these protected areas. This thesis explores the dynamic of participatory approach in protected area management. This thesis deals with the long overdue issue of local community versus protected area, by exploring one example pertinent to Malaysia which is the Taman Negara National Park and its neighbours. Briefly, it intends to examine the issues, concerns and opportunities of participatory approach in protected area management in Peninsular Malaysia. Specifically, it examines the benefits of community participation and its relationship with community acceptance on the types or levels of participation suitable in protected area management…